2021
DOI: 10.1016/j.ajem.2021.05.044
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac markers of multisystem inflammatory syndrome in children (MIS-C) in COVID-19 patients: A meta-analysis

Abstract: Objective A meta-analysis of laboratory cardiac markers for multisystem inflammatory syndrome in children (MIS-C) was performed in patients with coronavirus disease 2019 (COVID-19). Methods Eight databases were searched until April 10, 2021, for studies on cardiac markers, including B-type natriuretic peptide (BNP)/N-terminal pro-BNP (NT-proBNP), troponin, aspartate aminotransferase (AST), in MIS-C patients. Results Of the 2583 participants e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 50 publications
(93 reference statements)
3
33
1
2
Order By: Relevance
“…A meta-analysis also showed that the key cardiac marker in patients with MISC was BNP. 13 Although previously alluded to, 14,15 statistical analysis in this study conclusively shows that NT-proBNP and CRP levels are significantly higher among MISC patients in comparison to KD with elevation of these parameters; >935.7 and >99.55 mg/L at admission respectively might act as guides as to the need for more aggressive management.…”
Section: The Massive Activation Of Pro-inflammatory Cytokines In Miscmentioning
confidence: 49%
“…A meta-analysis also showed that the key cardiac marker in patients with MISC was BNP. 13 Although previously alluded to, 14,15 statistical analysis in this study conclusively shows that NT-proBNP and CRP levels are significantly higher among MISC patients in comparison to KD with elevation of these parameters; >935.7 and >99.55 mg/L at admission respectively might act as guides as to the need for more aggressive management.…”
Section: The Massive Activation Of Pro-inflammatory Cytokines In Miscmentioning
confidence: 49%
“…Our findings in non-MIS-C patients confirm previous findings that NT-proBNP is also elevated in systemic inflammation and might not only have a cardiac source [16]. A recent meta-analysis has shown higher BNP levels in MIS-C patients vs. non-severe COVID-19 infections and in patients with severe MIS-C vs. non-severe MIS-C. Abnormal levels did not correlate with direct coronary artery lesions; however, cardiac markers may be monitored longitudinally in admitted MIS-C patients to predict potential deterioration during the disease course [17].…”
Section: Discussionmentioning
confidence: 99%
“…Eine weitere Metaanalyse kommt zum Schluss, dass Patienten mit schwerem PIMS/MIS-C höhere Werte für pro-BNP im Vergleich zu Patienten mit milder COVID-19 Erkrankung und Patienten mit leichtem PIMS/MIS-C aufwiesen; für Troponin und ASAT ergaben sich hingegen keine Unterschiede zwischen diesen Patientengruppen. Interessanterweise waren die proBNP-und Troponinwerte bei Patienten mit PIMS/MIS-C mit und ohne Beteiligung der Koronararterien nicht signifikant verschieden [17].…”
Section: Klinik Und Diagnostik Bei Verdacht Auf Pimsunclassified